Indigenous Midwives and the Biomedical System among the Karamojong of Uganda: Introducing the Partnership Paradigm - Graham, Sally; Davis-Floyd, Robbie (Frontiers in Sociology, 2021)
Certainly there can be no argument against every woman being attended at birth by a skilled birth attendant. Currently, as elsewhere, the Ugandan government favors a biomedical model of care to achieve this aim, even though the logistical realities in certain regions mitigate against its realisation. This article addresses the Indigenous midwives of the Karamojong tribe in Northeastern Uganda and their biosocial model of birth, and describes the need British midwife Sally Graham, who lived and worked with the Karamojong for many years, identified to facilitate “mutual accommodation” between biomedical staff and these midwives, who previously were reluctant to refer women to the hospital that serves their catchment area due to maltreatment by the biomedical practitioners there. This polarisation of service does not meet that society’s needs. We do not argue for the provision of a unilateral, top-down educational service, but rather for one that collaborates between the biosocial model of the Karamojong and the biomedical model supported by government legislation. We show that such a partnership is practical, safer, and harnesses the best and most economical and effective use of resources. In this article, we demonstrate the roles of the Indigenous midwives/traditional birth attendants (TBAs) and show that not only is marriage of the two systems both possible and desirable, but is also essential for meeting the needs of Karamojong women. The TBA is frequently all the skilled assistance available to these women, particularly during the rainy season when roads are impassable in rural South Karamoja. Without this skilled help, the incidence of maternal and infant mortality would undoubtedly increase. Ongoing training and supervision of the TBA/Indigenous midwife in best practices will ensure better care. We offer a way forward via the Partnership Paradigm (PP) that lead author Sally Graham designed in conjunction with the Indigenous midwives and biomedical staff with whom she worked, the development and characteristics of which this article describes.